Państwo a ekonomika: [State and economics] (Studia Prawnicze / The Legal Studies, 1985)
For a long time human mind has been absorbed by the role of the state in the development of the society.Economic role of the state through the history, and, in particular its contemporary role lead to the conclusion that the çategories of base and superstructure in relation to the state do not make it possible to place it in the sphere of reality indicated by those categories.The state, understood as the organisation of the society divided into classes, performs both political functions (protection of the existing domineering mode of production) as well as economic ones (organizes economy, fixes paramétrés of economic activity, creates infrastructure for economic activity). At a certain stage of development of social production the state becomes an indispensable way of its organization and at the same time social existence of human population.As a consequence, the state, its activity cannot be totally placed in the base or superstructure, as understood by many Marxists. It is an element of the base and superstructure.Such a vision of the role of the state in the social development exerts also influence on hypotheses on its further development, its role in the future. Such a vision of the state may help to understand links between politics and economics.